Randomised controlled trial of a theory-based behavioural intervention to reduce formula milk intake. Issue 11 (14th May 2018) - Lakshman, Rajalakshmi; Sharp, Stephen J; Whittle, Fiona; Schiff, Annie; Hardeman, Wendy; Irvine, Lisa; Wilson, Ed; Griffin, Simon J; Ong, Ken K
Abstract : Objective: To assess the efficacy of a theory-based behavioural intervention to prevent rapid weight gain in formula milk-fed infants. Design: In this single (assessor) blind, randomised controlled trial, 669 healthy full-term infants receiving formula milk within 14 weeks of birth were individually randomised to intervention (n=340) or attention-matched control (n=329) groups. The intervention aimed to reduce formula milk intakes, and promote responsive feeding and growth monitoring to prevent rapid weight gain (≥+0.67 SD scores (SDS)). It was delivered to mothers by trained facilitators up to infant age 6 months through three face-to-face contacts, two telephone contacts and written materials. Results: Retention was 93% (622) at 6 months, 88% (586) at 12 months and 94% attended ≥4/5 sessions. The intervention strengthened maternal attitudes to following infant feeding recommendations, reduced reported milk intakes at ages 3 (−14%; intervention vs control infants), 4 (−12%), 5 (−9%) and 6 (−7%) months, slowed initial infant weight gain from baseline to 6 months (mean change 0.32 vs 0.42 SDS, baseline-adjusted difference (intervention vs control) −0.08 (95% CI −0.17 to −0.004) SDS), but had no effect on the primary outcome of weight gain to 12 months (baseline-adjusted difference −0.04 (−0.17, 0.10) SDS). By 12 months, 40.3% of infants in the intervention group and 45.9% in the control group showed rapid weight gain (OR 0.84, 95% CI 0.59 to 1.17). Conclusions: Despite reducing milk intakes and initial weight gain, the intervention did not alter the high prevalence of rapid weight gain to age 12 months suggesting the need for sustained intervention. Trial registration number: ISRCTN20814693 .